2011
DOI: 10.1111/j.1464-5491.2011.03510.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Vitamin D deficiency play a role in peripheral neuropathy in Type 2 diabetes?

Abstract: Vitamin D deficiency is an independent risk factor for diabetic peripheral neuropathy, and further studies are required to confirm if Vitamin D supplementation could prevent or delay the onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
116
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 25 publications
4
116
3
4
Order By: Relevance
“…DSPN was significantly associated with vitamin D deficiency after adjustment for diabetes duration, glycated hemoglobin, and LDLc (OR: 3.47. 95% CI: 1.04-11.56, p = 0.043) [83]. In a short, 8-week prospective study, the same authors demonstrated a significant (p < 0.001) improvement of neuropathic symptoms with oral vitamin D supplementation vs. placebo [84].…”
Section: Low Vitamin Dmentioning
confidence: 60%
See 3 more Smart Citations
“…DSPN was significantly associated with vitamin D deficiency after adjustment for diabetes duration, glycated hemoglobin, and LDLc (OR: 3.47. 95% CI: 1.04-11.56, p = 0.043) [83]. In a short, 8-week prospective study, the same authors demonstrated a significant (p < 0.001) improvement of neuropathic symptoms with oral vitamin D supplementation vs. placebo [84].…”
Section: Low Vitamin Dmentioning
confidence: 60%
“…In T2D, the level of vitamin D was found to be significantly lower in those patients with DSPN [83]. Of patients with DSPN, 81.5% had vitamin D deficiency compared with 60.4% of those without DSPN [83].…”
Section: Low Vitamin Dmentioning
confidence: 95%
See 2 more Smart Citations
“…The results of our study expand existing knowledge by showing prospectively in a large cohort that low blood 25OH-D is also a risk factor for development of peripheral neuropathy, retinopathy, nephropathy, and amputation. Previous cross-sectional studies reported lower circulating 25OH-D concentrations in diabetic patients with microvascular disease events (16)(17)(18)(19). However, all of these studies were limited by their size and design.…”
Section: Discussionmentioning
confidence: 99%